The War Against Corruption In Nigeria: The Problems with The Solution - Owolabi, Dare; Olaleye, Oluseyi I. (African Journal of Stability and Development (AJSD), 2018)
Corruption has become the most popular issue that is subjected to discussion by individuals, organisations and government officials in Nigeria. This is based on the position the cankerworm has occupied in the political system and its nefarious effects on the entire citizenry. The various administrations in Nigeria have put in place certain measures to curb corrupt practices among public officials having noticed the negative implications of the menace on the entire system. This work undertakes the conceptual clarification of corruption and proceeds to showcase the various anti corruption measures that have been put in place by succeeding regimes in Nigeria. These measures which represent the solutions by the government have yielded little or no positive impact on corrupt practices in the nation. This paper therefore discusses the problems with these anti corruption measures and finally submits that while administrative capacity is imperative in the fight against corruption, political will supersedes.